The Arthur of the Iberians. The Arthurian legends in Spanish and Portuguese worlds. Edited by David Hook. University of Wales Press, 2015. - Laranjinha, Ana Sofia (Guarecer. Revista Eletrónica de Estudos Medievais, 2018)
.